Après #MeToo : réflexions sur la construction de l'agentivité sexuelle de jeunes femmes ayant des relations sexuelles avec des hommes - Pratt-Dumas, Camille (Université du Québec à Montréal, 2023)
Ce travail de recherche s’attarde à répondre aux deux questions suivantes : d’abord, comment les jeunes femmes québécoises ayant des relations sexuelles avec des hommes perçoivent-elles l’influence des mouvements de dénonciations qui ont eu lieu dans les dernières années? Ensuite, qu’est-ce qui caractérise les réflexions sur leur agentivité sexuelle de ces jeunes femmes? S’inscrivant dans le contexte de la multiplication des mouvements de dénonciations de violences sexuelles, cette recherche tente de voir l’impact perçu que ces mouvements, et le contexte social particulier qui en résulte, peuvent avoir sur les jeunes femmes qui ont vécu leur entrée dans la sexualité dans ce contexte. L'objectif est de comprendre l’agentivité sexuelle de ces jeunes femmes telle qu'elles la vivent, et comment celle-ci est négociée dans un contexte hétéropatriarcal. J'explore également de quelles façons ces jeunes femmes, après ces campagnes médiatiques de sensibilisation, incorporent des éléments de cette culture contestataire dans leurs réflexions. À l’aide de questionnaires et d’entretiens semi-dirigés auprès de 8 jeunes femmes, nous avons recueilli des données sur ce sujet. Les résultats ont été interprétés à la lumière de la littérature sur l'agentivité sexuelle des femmes, dans une perspective féministe critique de l'hétérosexualité comme rapport de domination des hommes sur les femmes. Les résultats nous montrent que l’agentivité sexuelle se développe progressivement, au fil des expériences des jeunes femmes interrogées. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : agentivité sexuelle, jeunes femmes, hétérosexualité, sexualité des femmes, patriarcat, dénonciations en ligne
https://uqam-bib.on.worldcat.org/oclc/1378171039
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; agentivité sexuelle; amériques; approches et analyses; discipline; hétérosexisme; jeunes femmes*; metoo; mémoires/thèses; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sexualité; sexualité des femmes*; sociologie; systèmes d'oppressions; thématiques; étude qualitative

"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit

“Stay the fuck at home!”: Feminism, family and the private home in a time of coronavirus - Kay, Jilly Boyce (Feminist Media Studies, 2020)
This short essay considers how, in conditions of widespread lockdown during the coronavirus pandemic, domestic space has become hyper-visible. It argues that, in the mediated aesthetics of the crisis, we have seen a resurgence of mystificatory images of the heteronormative private household through celebrity culture. It considers how the injunction to ‘stay the fuck at home’ may work to conceal pervasive forms of gendered violence within domestic space, as well as re-affirming the private, capitalist home as a place of safety and stability. Drawing on the work of family abolitionist feminism, the essay argues that we might turn the hyper-visibility of the private heteronormative home against itself, by exposing its inbuilt dangers, inequalities, and cruelties - and by imagining how much better home could be.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; communication; covid-19; discipline; espace domestique; hétérosexisme; inégalités; périodes historiques; représentations médiatiques; ressource en ligne; systèmes d'oppressions; thématiques; violences

Comment la crise fait-elle ressortir les inégalités de genre ? - Plumauzille, Clyde (2020)
Aides-soignantes, caissières, aides à domicile… ce sont majoritairement des femmes qui se retrouvent en première ligne contre le virus. Comme le rappelle l’historienne Clyde Plumauzille dans ce podcast, ces inégalités ne sont pas nouvelles, la prise en charge d’autrui au sein du foyer ou dans la société étant historiquement dévolue aux femmes.
Performers: _:n2788
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; charge mentale; confinement; covid-19; histoire et politique; hétérosexisme; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; travail; travail domestique; violences; violences conjugales